2020
DOI: 10.48550/arxiv.2010.10633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamical Evolution and Thermal History of Asteroids (3200) Phaethon and (155140) 2005 UD

Eric M. MacLennan,
Athanasia Toliou,
Mikael Granvik

Abstract: The near-Earth objects (NEOs) (3200) Phaethon and (155140) 2005 UD are thought to share a common origin, with the former exhibiting dust activity at perihelion that is thought to directly supply the Geminid meteor stream. Both of these objects currently have very small perihelion distances (0.140 and 0.163 au for Phaethon and 2005 UD, respectively), which results in them having perihelion temperatures of or exceeding 1000 K. NEO population models compared to discovery statistics suggest that low-perihelion obj… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 114 publications
(186 reference statements)
0
6
0
Order By: Relevance
“…Still, Bennu stands as another interesting example of unexpected forms of activity on NEOs in addition to Phaethon. MacLennan et al (2020) describe the long-term evolution of the thermal history of Phaethon, showing that it experiences cyclical changes to its maximum heating from the Sun. Based on those results, Phaethon currently is just past the peak of its ∼ 18 kyr heating cycle, which would imply that sodium volatilization should be ramping down.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, Bennu stands as another interesting example of unexpected forms of activity on NEOs in addition to Phaethon. MacLennan et al (2020) describe the long-term evolution of the thermal history of Phaethon, showing that it experiences cyclical changes to its maximum heating from the Sun. Based on those results, Phaethon currently is just past the peak of its ∼ 18 kyr heating cycle, which would imply that sodium volatilization should be ramping down.…”
Section: Discussionmentioning
confidence: 99%
“…Any ice thermally coupled to the surface would be expected to have been removed quickly after Phaethon's dynamical transfer into its current orbit, and not survive to the present day. MacLennan et al (2020) have shown that over the course of its orbital evolution Phaethon has undergone numerous cycles through high peak temperatures like today, which would have baked off any water near the surface. This means water ice cannot be driving the observed activity, which is seen only in a short temporal period around Phaethon's perihelion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given Phaethon's non-zero inclination and high eccentricity, the number of plausible parent bodies or families is not extremely numerous. The recent work by MacLennan et al 2020 shows that the high-inclination inner Main Belt Svea family might be a better match than previous candidates like the family of (2) Pallas (de León et al 2010), so further characterization of objects in that family is of interest.…”
Section: The Origin Of the Geminids?mentioning
confidence: 96%
“…If the two objects really are only coincidentally similar, then there should be multiple pathways into Phaethon / Geminid -like orbits. While there are serious issues to be resolved in understanding whether or not Phaethon is a heated and devolatilized member of the Pallas Collisional Family (de León et al 2010;Kareta et al 2018;MacLennan et al 2020), 2005 UD's spectrum is a very poor match for Pallas or any member of the Pallas Collisional Family (they are all strongly blue in the near-infared, many with Phaethon-like concave up spectra), suggesting that those problems would be even more challenging to resolve for it. Furthermore, the surface of the less studied candidate member of the Phaethon-Geminid-Compolex 1999 YC (Ohtsuka et al 2008) is an even worse fit (Kasuga & Jewitt 2008), so the problems continue in that arena.…”
Section: Phaethon Vs 2005 Udmentioning
confidence: 99%